Edema quantification by computerized morphometry as an evaluation parameter for the resistance of colon anastomoses - Priolli,Denise Gonçalves (2003)
PURPOSE: This work had the objective of verifying the validity of using computerized morphometry as a method of quantitative analysis of the interference of edema in scar formation following colon anastomosis. METHODS: Forty-five adult female Wistar rats were utilized, divided into three groups of 15 animals according to whether sacrifice was performed on the first, second or seventh postoperative day. Each group was subdivided into a main group consisting of 10 animals, and a control group consisting of five animals. In the main group, in addition to the quantitative computerized morphometric analysis of the edema in the submucosal layer, the resistance of the colon anastomosis to bursting strength was verified. In the control group, edema quantification was studied alone. RESULTS: The results found via the computerized morphometry method showed that there is a 7% decrease in the presence of edema during the first postoperative week. They confirmed that there is an inverse statistically significant relationship (p< 0.001) between edema presence and the resistance of the anastomosis to bursting strength. CONCLUSION: The use of computerized morphometry is a reliable, fast, objective and low-cost methodology for the quantification of edema in colon anastomoses.